Penerapan Pengendalian Mutu Produksi Dengan Statistical Quality Control (SQC) Dan Six Sigma Pada Liberty Shoes Kota Padang - Ika Haryani; Muthia Roza Linda (Universitas Negeri Padang, 2019)
This study aims to identify defects that occur during the production process, to find out how the quality control of production with Statistical Quality Control (SQC) and Six Sigma and the factors that cause damage/disability in the production process. This research includes descriptive research that aims to study the aspects of who, what, when and how of a topic. By using the Statistical Quality Control (SQC) method, it can be seen whether the production is in a controlled or uncontrolled state. While Six Sigma is to find solutions and improve the quality of product processes so that the number of defective products can be reduced. Based on calculations with Statistical Quality Control (SQC) method that Liberty Shoes production is still uncontrolled, that is, there is a disability value of 3.193% and using P (P-Chart) control diagrams it can also be seen that there is still a proportion of disability that is beyond the control limit. The results of the Six Sigma analysis revealed that the sigma level was 3.91 sigma or 7,964.60 defective products from one million production. Based on the Pareto diagram it is known that the highest disability level is sequentially 47.11%, Cutting 20.79%, Stitching 16.17% and Policing 15.94%. While the causes of disability are based on the Cause and Effect diagram, namely human factors, methods, machinery, materials and environment Keywords: Statistical Quality Control, Sig Sigma, DPMO